Pre-stroke undiagnosed dysphagia lusoria as a rare cause of aspiration pneumonia with respiratory failure in a stroke patient - Spatenkova, Vera; Krejzarova, Pavlina; Jedlicka, Jaroslav (SAGE open medical case reports, 2018)
Introduction: Dysphagia is a risk factor for aspiration pneumonia and acute respiratory failure in acute stroke patients. Dysphagia lusoria is caused by compression on the esophagus from artery lusoria, when the aberrant right subclavian artery arises from the descending aortic arch. We present a rare case report of pre-stroke undiagnosed dysphagia lusoria as a cause of aspiration pneumonia with acute respiratory failure in a 67-year-old female patient admitted with a minor left intracerebral hemorrhage in the left basal ganglia. On admission to the stroke unit, she had Glasgow Coma Scale of 15, National Institutes of Health Stroke Scale of 8, and a negative screening test for dysphagia, dysphasia, and right-sided hemiparesis. After 16 h of admission, dyspnea suddenly occurred with a decrease in SpO2(72%). X-ray of the lungs showed less ventilated areas of the lung due to aspiration pneumonia and a broad disfigured shadow of the anterior mediastinum on the base of the lusoria artery. Dysphagia lusoria was confirmed by spiral computed tomography angiography. Conclusion: One aim of neurocritical care is the prevention of pneumonia from dysphagia due to risk of acute respiratory failure and secondary brain damage. Pre-stroke undiagnosed dysphagia lusoria could be one very rare cause. A broad disfigured shadow of the anterior mediastinum in X-ray of the lungs gives rise to the first suspicion of the possibility of dysphagia lusoria.